The battle for social security : - Altman, Nancy J. (J. Wiley, 2005)
This history of the Social Security system by Altman (Chairman of the Board of Directors, Pension Rights Center) can be seen as an antidote to the misinformation billowing out of the Bush White House in its efforts to transform the program. She takes readers from the first glimmerings of the program in the minds of the policy makers to the current debates over whether it is going bankrupt. Along the way, she details how opponents of the system, including George W. Bush's father and grandfather, having used arguments remarkably similar to those heard today in order to weaken or eliminate the program. She also offers her own advice on how the program can be strengthened in line with the program's original philosophy.